Individual-specific levels of CTG•CAG somatic instability are shared across multiple tissues in myotonic dystrophy type 1 - Morales Montero, Fernando (2023)
Myotonic dystrophy type 1 is a complex disease caused by a genetically unstable CTG repeat expansion in the 3′-untranslated region of the DMPK gene. Age-dependent, tissue-specific somatic instability has confounded genotype–phenotype associations, but growing evidence suggests that it also contributes directly toward disease progression. Using a well-characterized clinical cohort of DM1 patients from Costa Rica, we quantified somatic instability in blood, buccal cells, skin and skeletal muscle. Whilst skeletal muscle showed the largest expansions, modal allele lengths in skin were also very large and frequently exceeded 2000 CTG repeats. Similarly, the degree of somatic expansion in blood, muscle and skin were associated with each other. Notably, we found that the degree of somatic expansion in skin was highly predictive of that in skeletal muscle. More importantly, we established that individuals whose repeat expanded more rapidly than expected in one tissue (after correction for progenitor allele length and age) also expanded more rapidly than expected in other tissues. We also provide evidence suggesting that individuals in whom the repeat expanded more rapidly than expected in skeletal muscle have an earlier age at onset than expected (after correction for the progenitor allele length). Pyrosequencing analyses of the genomic DNA flanking the CTG repeat revealed that the degree of methylation in muscle was well predicted by the muscle modal allele length and age, but that neither methylation of the flanking DNA nor levels of DMPK sense and anti-sense transcripts could obviously explain individual- or tissue-specific patterns of somatic instability.